Retrospective Evaluation of Outcome in Dogs With Appendicular Osteosarcoma Following Hypofractionated Palliative Radiation Therapy With or Without Bisphosphonates: 165 Cases (2010–2019) - Ringdahl-Mayland, Beck; Thamm, Douglas H.; Martin, Tiffany W. (Frontiers in Veterinary Science, 2022)
Objective: To report the survival times in dogs that received a standardized palliative-intent radiation therapy (RT) protocol for the treatment of canine appendicular osteosarcoma (OSA), alone or in combination with bisphosphonates (BPs), and to determine whether the addition of BPs affects survival. A secondary objective was to identify prognostic features that may influence outcome in dogs undergoing treatment. Design: Retrospective case series. Materials and Methods: Dogs with presumed or confirmed OSA of the appendicular limb treated with daily hypofractionated RT (8 Gy x 2) at the Flint Animal Cancer Center between 2010 and 2019 were evaluated retrospectively. Clinical data were abstracted from the medical records, and adjuvant therapies were noted. Outcome was assessed using medical records and electronic follow up. Results: One hundred and sixty-five dogs were included. Sixty-eight dogs received BPs as a part of their palliative-intent treatment. The median survival time from first RT treatment to death was not significantly different between groups (119 vs 109 days for BP and non-BP groups respectively, p=0.758). Only age (> 9 years) was found to be prognostic in this population (p=0.031). Factors that were not found to be associated with survival time included BP drug type, timing of BP administration, tumor location, weight, breed, sex, time to treatment, concurrent administration of chemotherapy, and salvage amputation. Conclusions: This study suggests no difference in outcome for dogs treated with and without BPs in addition to hypofractionated RT. Prospective studies are needed to determine if the addition of BPs to hypofractionated RT leads to an improved quality of life in dogs undergoing palliative-intent treatment for OSA.